John Philoponus' new definition of prime matter : aspects of its background in Neoplatonism and the ancient commentary tradition - Haas, Frans A. J. de, 1963-. (Philosophia Antiqua, 1997)
This study provides the first full discussion of Philoponus' excursus on matter in contra Proclum XI. 1-8 which sets out the innovative definition of prime matter as three-dimensional extension. The author argues that Philoponus' definition was motivated primarily by philosophical problems in Neoplatonism. Philoponus employs the explanation of growth, the interpretation of Aristotle's category theory and the notions of formlessness and potentiality to substantiate his definition. To conclude, the book offers an assessment of the significance of Philoponus' innovation. It is demonstrated for the first time that Plotinus' view of matter exerted considerable influence on both Philoponus and Simplicius. Moreover, the structure of Syrianus' and Proclus' metaphysics prepared the way for Philoponus' account of prime matter.